Sorption removal of uranium (VI) compounds with organic-inorganic ion-exchangers - Perlova, Natalia; Perlova, Olga; Halutska, Iryna; Dzyazko, Yulia; Palchik, Alexey; Sazonova, Valentina (My University, 2016)
Organic-inorganic composites based on ion exchange resins containing zirconium hydrophosphate (cation-exchanger) and hydrated zirconium dioxide (anion-exchanger) were applied to removal of soluble U(VI) compounds from modeling solutions. The advantages of the composites over the pristine resins are more significant sorption capacity, higher sorption rate and more facile regeneration.
Keywords: organic-inorganic ion-exchangers; zirconium hydrophosphate; hydrated zirconium dioxide; uranyl ions; waste water treatment; органо-неорганічні іоніти; гідрофосфат цирконію; гідратований діоксид цирконію; йони уранілу; очистка стічних вод; органо-неорганические иониты; гидрофосфат циркония; гидратированный диоксид циркония; ионы уранила; очистка сточных вод